Force analysis of slope reinforced by Frame-Anchor-Support-Structure based on improved horizontal slice method - Guang-Wen Fang; Fei Guo; An-Ping Huang (PLoS ONE, 2025)
As a flexible support structure commonly used in slope stabilization and management, the Frame-Anchor-Support-Structure (FASS) is of great significance in studying the actual stress situation to ensure the safety of slopes. In this paper, based on the traditional horizontal slice method, utilizing the principle that the vertical slice method and the horizontal slice method share the same sliding surface, the inter-strip force between soil slices, the effect of the FASS, the effect of the slope-top uniform load, and the relationship between the vertical slice method and the horizontal slice method of the force conversion is considered at the same time. The improved horizontal slice method for the slope reinforced by the FASS is also proposed, and the force calculation formula for the slope reinforced by FASS is derived. By comparing and analyzing with the overall sliding wedge method, the reasonableness and accuracy of the calculation method of this paper are verified, and the variety rule of force on the slope reinforced by FASS under different loads is obtained. The results show that the combined force of lateral earth pressures on slopes calculated in this paper is smaller than that of the overall sliding wedge method, but the difference between the two is not significant (within 9% difference). The earth pressure strength of the slope, the shear stress of FASS on the sliding soil, and the vertical force strength and the shear stress of the stabilized soil on the sliding soil all show a distribution trend of small at both ends and large in the middle (about 1/3 of the position from the bottom of the slope). Moreover, the trend of the above forces does not vary with the slope-top uniform loads. The study results are informative for calculating and analyzing the forces on the slope reinforced by FASS.